Emerging strategies and therapies for treatment of Paget’s disease of bone - Brown JP; Michou L (Dove Medical Press, 2011)
Laëtitia Michou, Jacques P BrownLaval University, Department of Medicine, CHUQ (CHUL) Research Centre and Division of Rheumatology, Quebec City, QC, CanadaAbstract: Paget’s disease of bone (PDB) is a progressive monostotic or polyostotic metabolic bone disease characterized by focal abnormal bone remodeling, with increased bone resorption and excessive, disorganized, new bone formation. PDB rarely occurs before middle age, and it is the second most frequent metabolic bone disorder after osteoporosis, affecting up to 3% of adults over 55 years of age. One of the most striking and intriguing clinical features is the focal nature of the disorder, in that once the disease is established within a bone, there is only local spread within that bone and no systemic dissemination. Despite many years of intense research, the etiology of PDB has still to be conclusively determined. Based on a detailed review of genetic and viral factors incriminated in PDB, we propose a unifying hypothesis from which we can suggest emerging strategies and therapies. PDB results in weakened bone strength and abnormal bone architecture, leading to pain, deformity or, depending on the bone involved, fracture in the affected bone. The diagnostic assessment includes serum total alkaline phosphatase, total body bone scintigraphy, skull and enlarged view pelvis x-rays, and if needed, additional x-rays. The ideal therapeutic option would eliminate bone pain, normalize serum total alkaline phosphatase with prolonged remission, heal radiographic osteolytic lesions, restore normal lamellar bone, and prevent recurrence and complications. With the development of increasingly potent bisphosphonates, culminating in the introduction of a single intravenous infusion of zoledronic acid 5 mg, these goals of treatment are close to being achieved, together with long-term remission in almost all patients. Based on the recent pathophysiological findings, emerging strategies and therapies are reviewed: ie, pulse treatment with zoledronic acid; denosumab, a fully human monoclonal antibody directed against RANK ligand; tocilizumab, an interleukin-6 receptor inhibitor; odanacatib, a cathepsin K inhibitor; and proteasome and Dickkopf-1 inhibitors.Keywords: Paget’s disease of bone, bisphosphonates, sequestosome 1, p62, autophagy, pathogenesis, interleukin-6